2021
DOI: 10.1111/jasp.12827
|View full text |Cite
|
Sign up to set email alerts
|

Communicating expert consensus increases personal support for COVID‐19 mitigation policies

Abstract: The Gateway Belief Model (GBM) places perception of a scientific consensus as a key “gateway cognition” with cascading effects on personal beliefs, concern, and ultimately support for public policies. However, few studies seeking to evaluate and extend the model have followed the specification and design of the GBM as originally outlined. We present a more complete test of the theoretical model in a novel domain: the COVID‐19 pandemic. In a large multi‐country correlational study ( N = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…First, regarding the three different topics, we found that the effects of scientific-consensus communication were very similar for climate change and genetically modified food. We identified only two experiments that investigated scientific-consensus communication in the context of vaccination (although more research might be upcoming because of the COVID-19 pandemic; e.g., Kerr & van der Linden, 2022), which prevents us from drawing conclusions regarding that topic specifically. Second, regarding extreme and influential cases, the main results related to perceived scientific consensus might be inflated somewhat (removal of extreme, influential, or potentially inflated effect sizes yielded g s of 0.44 and 0.46), whereas the effect related to belief in scientific facts was largely robust in this context.…”
Section: Discussionmentioning
confidence: 99%
“…First, regarding the three different topics, we found that the effects of scientific-consensus communication were very similar for climate change and genetically modified food. We identified only two experiments that investigated scientific-consensus communication in the context of vaccination (although more research might be upcoming because of the COVID-19 pandemic; e.g., Kerr & van der Linden, 2022), which prevents us from drawing conclusions regarding that topic specifically. Second, regarding extreme and influential cases, the main results related to perceived scientific consensus might be inflated somewhat (removal of extreme, influential, or potentially inflated effect sizes yielded g s of 0.44 and 0.46), whereas the effect related to belief in scientific facts was largely robust in this context.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, their selective rejection might be linked to pre-existing attitudes and the politicization and polarization of COVID-19 communication. Based on prior studies, it could be fruitful to develop interventions that use value-congruent messages ( Kahan et al, 2011 ), scientific consensus messages ( Kerr & Linden, 2022 ), or specifically warn about the politicization of science ( Bolsen & Druckman, 2015 ). For approvers, interventions should aim at increasing discernment between substantiated and unsubstantiated claims.…”
Section: Discussionmentioning
confidence: 99%
“…First, regarding the three different topics, we found that the effects of scientific consensus communication were very similar for climate change and genetically modified food. We identified only two experiments that investigated scientific consensus communication in the context of vaccination (although more research might be upcoming due to the COVID-19 pandemic, e.g., Kerr & van der Linden, 2021), which prevents us from drawing conclusions regarding this topic specifically. Second, regarding extreme and influential cases, the main results related to perceived scientific consensus might be inflated somewhat (removal of extreme, influential, or potentially inflated effect sizes yielded g's of 0.44 and 0.46), while the effect related to belief in scientific facts is largely robust in this context.…”
Section: Discussionmentioning
confidence: 99%